The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1016/j.jds.2011.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Dental and periodontal health status of subjects with sickle cell disease

Abstract: Background/purpose: Sickle cell disease (SCD) is a chronic, hereditary, autosomal recessive disorder. The pathophysiology of SCD is thought to result from polymerization of hemoglobin S in red blood cells under hypoxic conditions, which results in vaso-occlusion. The aim of this study was to determine the periodontal and dental health status of patients with SCD. Materials and methods: Fifty-five SCD patients and 41 healthy individuals were evaluated. Detailed medical and dental histories were taken, and a rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 48 publications
2
39
2
1
Order By: Relevance
“…Our results indicated no correlation between SCA and periodontal diseases, a finding already observed in the majority of previous studies . It has been reported that inflammatory conditions and severity of periodontal diseases in individuals with SCA seem to be correlated with oral hygiene conditions but not with the haematological disorder .…”
Section: Discussionsupporting
confidence: 48%
“…Our results indicated no correlation between SCA and periodontal diseases, a finding already observed in the majority of previous studies . It has been reported that inflammatory conditions and severity of periodontal diseases in individuals with SCA seem to be correlated with oral hygiene conditions but not with the haematological disorder .…”
Section: Discussionsupporting
confidence: 48%
“…Patients preoccupied with their major life threatening condition, therefore neglecting a basic preventive dental care. 11 Another reason could be because of the increased sensitivity to local factors (oral hygiene, tooth brushing habit and frequency of sugar intake). 12 The present study also showed that prevalence of dental caries was significantly higher in thalassemia patients than in age matched healthy controls, suggesting a need for restorative dental care in thalassemia children.…”
Section: Discussionmentioning
confidence: 99%
“…En cuanto a los hallazgos clínicos orales, aunque muchos autores no reconocen la condición periodontal como un factor predisponente de ACF (33,34), se puede generar una asociación entre las dos enfermedades cuando se relacionan con otros signos clínicos orales (35). Clínicamente, la paciente del caso reportado y sus hermanos presentaron surcos periodontales activos, palidez palatal y sangrado gingival al cepillado, este último fue el motivo de consulta.…”
Section: Discussionunclassified